2018
DOI: 10.1002/ijgo.12485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of premature luteinizing hormone increases among high ovarian responders undergoing a gonadotropin‐releasing hormone antagonist ovarian stimulation protocol

Abstract: Earlier administration of GnRH antagonist could avoid premature luteinizing hormone increases among high ovarian responders, especially those with a starting AFC of 22 or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
20
2
Order By: Relevance
“…( 8 ) and Geng et al. ( 15 ) both reported a high incidence of premature LH rises (15.6 and 16.2%, respectively), whereas another study, involving ganirelix, showed a much lower incidence (1.4%) ( 16 ). In the present study, 82 patients (8.03%) showed premature LH increases during GnRH antagonist treatment; this finding was in line with those of Dovey et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…( 8 ) and Geng et al. ( 15 ) both reported a high incidence of premature LH rises (15.6 and 16.2%, respectively), whereas another study, involving ganirelix, showed a much lower incidence (1.4%) ( 16 ). In the present study, 82 patients (8.03%) showed premature LH increases during GnRH antagonist treatment; this finding was in line with those of Dovey et al.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of a premature LH rise on pregnancy outcome remains controversial. A prospective study of 314 high ovarian responders undergoing a fixed GnRH-antagonist protocol, showed a lower clinical pregnancy rate in patients experiencing a premature rise in LH ( 15 ). The same result was found in women undergoing the flexible GnRH antagonist protocol; similarly, reduced rates of ongoing pregnancy rate were also reported previously ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore reasonable to conclude that a portion of the excessive responders in this study might be diagnosed with PCOS. Geng et al [ 28 ] reported that 21% of PCOS patients show premature luteinization, especially before follicle maturation, suggesting poor oocyte quality in PCOS patients [ 29 ]. Additionally, the metabolic similarities observed in the follicle fluid between excessive responders and PCOS patients indicate that metabolic alteration, among other things, could impair the quality of at least a portion of oocytes and embryos in excessive responders [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study was conducted in patients in whom hyper response is predicted with higher antral follicle count (≥ 15) in GnRH antagonist cycles. Lower 2 pronuclear embryo rate (P = 0.038), and fewer high-quality embryos (P = 0.020) were encountered in patients with PL [47]. On the other hand, it was suggested that PL results from diminished ovarian reserve, and is more common in poor responders and older women [48].…”
Section: Patient Profilementioning
confidence: 99%